Numerical methods in finance - Breton, Michèle.; Ben-Ameur, Hatem; GERAD (New York : Springer, 2005)
This book presents some exciting developments arising from the combination of mathematics, numerical analysis, and finance. It covers a wide range of topics, from portfolio management and asset pricing, to performance, risk, debt and real option evaluation. It also presents applications of a variety of cutting edge approaches and techniques, including robust control, min-max optimisation, Bessel processes, stochastic viability, variational inequalities, and Monte-Carlo test techniques. The book also presents surveys of models and approaches in specific areas in finance, such as corporate debt valuation and portfolio selection.
Includes bibliographical references.
sms 08/05/2018
Loans
Keywords: Finance